Psalm 32 - ’n eksegeties-teologiese verkenning: sondebelydenis is sondevergifnis! - Snyman, SD (Nederduitse Gereformeerde Teologiese Tydskrif, 2003)
Psalm 32 is subjected to an exegesis of the text focussing on text intern (demarcating the psalm; a text-critical investigation and an exploration of some structural features special to the psalm) and text extern (determining the Gattung and Sitz im Leben; tradition and redactional critical) facets. A structural analysis reveals that the psalm is made up of six strophes that in their turn may be grouped into four stanzas comprising of verses 1-2, 3-7, 8-10 and 11. The Gattung or literary genre of the psalm can be described as a mixture of an individual thanksgiving song, coupled with elements typical of wisdom literature. Three stages in the development of the psalm can be detected. Initially the psalm consisted of verses 3-7; later it was framed by verses 1-2 and 8-10, and at a still later stage verse 11 was added.